2021
DOI: 10.1177/00033197211026420
|View full text |Cite
|
Sign up to set email alerts
|

The ATRIA and Modified-ATRIA Scores in Evaluating the Risk of No-Reflow in Patients With STEMI Undergoing Primary Percutaneous Coronary Intervention

Abstract: The no-reflow (NR) phenomenon is frequently encountered in acute coronary syndrome. We evaluated the association between anticoagulation and risk factors in atrial fibrillation (ATRIA) and modified ATRIA risk scores and NR in ST-elevation myocardial infarction (STEMI). Consecutive patients (n = 551) who underwent primary percutaneous coronary intervention between December 2019 and June 2020 due to STEMI were included. The mean age of the patients was 60.5 ± 10.8 years (n = 369, 67% male). The ATRIA and modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Çetinkal et al 11 suggested that the ATRIA score can predict long-term adverse events in myocardial infarction patients and prognostic assessment can be made with the ATRIA score. Abacıoğlu et al 13 have shown that the ATRIA score may predict no-reflow in patients undergoing primary PCI and may be associated with microvascular dysfunction. Another recent study suggested that the ATRIA score might be useful in predicting contrast-induced nephropathy (CIN) in STEMI patients who underwent primary PCI and that patients at high risk for CIN could be detected by using the ATRIA score in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Çetinkal et al 11 suggested that the ATRIA score can predict long-term adverse events in myocardial infarction patients and prognostic assessment can be made with the ATRIA score. Abacıoğlu et al 13 have shown that the ATRIA score may predict no-reflow in patients undergoing primary PCI and may be associated with microvascular dysfunction. Another recent study suggested that the ATRIA score might be useful in predicting contrast-induced nephropathy (CIN) in STEMI patients who underwent primary PCI and that patients at high risk for CIN could be detected by using the ATRIA score in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the ATRIA risk score is associated with adverse clinical outcomes in patients with acute coronary syndrome (ACS). 11 13 …”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] Previous research has also demonstrated the NR connection of another risk score, ATRIA (the Anticoagulation and Risk Factors in Atrial Fibrillation), and its modified versions. 29 The HAT 2 CH 2 score, based on the patient's age and the presence of HT, stroke or transient ischemic attack, COPD, and HF, was developed in 2010 to identify patients likely to progress to sustained forms of AF. 10 The HAT 2 CH 2 score, in other words, is a scoring system that intends to demonstrate the development of chronic disease and advanced age-related risk factors to new AF without relying on laboratory results.…”
Section: Discussionmentioning
confidence: 99%
“…These two risk scores mainly consist of patient-related risk factors. Since CCS patients were included in the present stu- Although these risk scores were designed primarily to predict thrombo-embolism in AF, they were used in different cardiac conditions regardless of being in AF rhythm [16,[31][32][33][34]. CHA 2 DS 2 -VASc was found to have effective discriminating power in determining CIN development in STEMI patients [35].…”
Section: Discussionmentioning
confidence: 99%